Czechia-Bavaria and Cross-Border Possibilities of Cooperation at the Faculty of Education in the Technical Field - Zadražilová, Alice; Simbartl, Petr; Krotký, Jan (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
The article is focused on the cooperation between Czech and Bavarian faculties educating future teachers. The process of studying education in Bavaria is briefly introduced. By comparing the Bavarian way of educating teachers in Bavaria and in the Czech Republic, our view on the cooperation, which was from the geographical point of view suitable for further research cooperation for our faculty, is negative. The way of education is so different and it is not possible to expand our cooperation into a bigger dimension. For the future, the possibility is open just for very specific topics.